Peran E-Wom Dan Brand Image Terhadap Loyalitas Di Desa Wisata Kabupaten Pamekasan - Dwi Nur Cholifah; Fathor AS (Journal Of Business, Finance, and Economics (JBFE), 2023)
This research was conducted with the aim of determining the role of Electronic Word of Mouth (E-WOM) and brand image on visitor loyalty through tourist visiting decisions. The method used in this study is quantitative descriptive method. The samples taken were visitors to Bukit Kehi Tourism as many as 115 people by applying accidental sampling techniques. Data in the study were obtained from primary data through the distribution of questionnaires and also secondary data sourced from literature related to the object of research. The data analysis technique used is Partial Last Square. The results of this study stated that E-WOM (X1) has a significant effect on visiting decisions (Z), Brand image (X2) has a significant effect on visiting decisions (Z), E-WOM (X1) has a significant effect on visitor loyalty (Y), Brand image (X2) does not have a significant effect on visitor loyalty (Y), and visiting decisions have a significant effect on visitor loyalty (Y).